PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUASAN PELANGGAN DAN MINAT BELI ULANG PADA PRODUK KREDIT CEPAT AMAN (KCA) DI PT. PEGADAIAN (PERSERO) CABANG PALU SELATAN - Samuel Supit, Victor (Katalogis, 2015)
The purpose of this research are: 1) to determinate the influence of service marketing mix towards customer satisfaction and customer repurchase intention on secure instant credit in PT. Pegadaian (Persero) Branch South Palu; 2) to determinate the influence of customer satisfaction towards, customer repurchase intention on Secure Instant Credit (Kredit Cepat Aman) in PT. Pegadaian (Persero) Branch South Palu. The research is causal descriptive that explains the relationship between variables by involving 192 respondents. Sampling method used is systematic random sampling. Analysis method is Structural Equation Modelling (SEM).Â  The results show that: 1) service marketing mix significantly affects customer satisfaction; 2) customer satisfaction significantly affects customer repurchase intention.